Implementation of Spiritual Guidance in Fostering Student Independence at Al-Karomah Aidarusy Sibiruang Islamic Boarding School - Saputra, Andri; Dewi, Eva; Moenanda, Meimunah S (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the implementation of spiritual guidance in fostering the independence of students at the Alkaromah Aidarusy Islamic Boarding School. The main focus of the research is to identify how spiritual guidance is applied practically as well as the specific methods used to achieve student independence. This research is important considering the strategic role of pesantren in shaping the character and independence of students through holistic education that integrates religious, intellectual, spiritual and social aspects. This type of research is a case study (Case Study) which is carried out with a qualitative approach to understand the phenomenon in depth. Then, in the implementation of this qualitative research, a descriptive method will be used to present the findings in the form of a detailed description of how spiritual guidance is applied and how it impacts the independence of students at the pesantren. And this research will collect data through observation, in-depth interviews with caregivers, ustadz/ustadzah, and several students, the results of this study show that spiritual guidance has been carried out well which is carried out through several methods in each activity, including the advice method that forms behavioral independence, group method that forms social independence and habituation method that forms habituation in worship without must participate (Taklid).